Urbano Orad y Gajías (1849-1935): Medical, War Hero and Freemason - de Paz Sánchez, Manuel Antonio (2018)
This biographical note aims to reflect on some aspects of the military doctor and colonel, Urbano Orad y Gajías’s life. He is a leading figure in the history of the Military Health of Spain. He fought in the wars of Cuba and North Africa, at the turn of the 20th century, and earned the highest military reward granted in Spain. We have also studied his relationship with Freemasonry, his reformist ideas and his active participation in important socio-cultural events such as the Second Congress of Africanist (Zaragoza, 1908). In addition, we have compared his biography with other prominent figures from the same period. They combined their reformism and critical spirit with a high sense of Spanish patriotism, in an environment marked by Spain’s 1898 regeneration movement.